NHERI@UTexas experimental facility with large-scale mobile shakers for field studies: a decade of discovery in natural hazards engineering - Stokoe, Kenneth H.; Hwang, Sungmoon; Cox, Brady R.; Clayton, Patricia M.; Gilbert, Robert B. (Frontiers in Built Environment, 2025)
IntroductionNatural hazards present significant risks to infrastructure and communities, emphasizing the importance of advanced tools and methods to better understand and mitigate these challenges. The Natural Hazards Engineering Research Infrastructure (NHERI) experimental facility at the University of Texas (NHERI@UTexas), funded by the National Science Foundation (NSF), addresses this need by offering unique resources for large-scale field testing.MethodsNHERI@UTexas contributes unique, large-scale, literally one-of-a-kind, mobile dynamic shakers and associated instrumentation to investigate seismic, cyclic, and static in-situ testing. These capabilities allow researchers to conduct experiments on actual infrastructure and geotechnical systems under real-world conditions, often impossible to accurately simulate in the laboratory.ResultsNHERI@UTexas has supported pioneering research in several areas, including: (1) enhanced 2D/3D geotechnical and seismic subsurface imaging, (2) in-situ characterization of liquefaction resistance and nonlinear dynamic soil behavior, (3) development of in-situ nondestructive soil-foundation-structure interaction (SFSI) methods, and (4) rapid geotechnical assessments following natural hazard events. These efforts have advanced the validation and calibration of numerical model and methodologies using full-scale experimental data.DiscussionNHERI@UTexas enable researchers to gain new insights and drive innovations in advancing resilient and sustainable solutions for natural hazards problems.